Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1088/1674-1056/20/9/098503
|View full text |Cite
|
Sign up to set email alerts
|

The advantage of blue InGaN multiple quantum wells light-emitting diodes with p-AlInN electron blocking layer

Abstract: Lu Tai-Ping( ) a) , Li Shu-Ti(Wu Le-Juan( ) a) , Wang Hai-Long( ) a) , and Yang Xiao-Dong( ) a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 14 publications
(10 reference statements)
1
15
0
Order By: Relevance
“…[13] The intra-band relaxing rate is determined to be 1×10 −13 s. [14] By carefully choosing the specific material parameters, APSYS can be used to explore the internal physical process and in optimizing device performances. [15,16]…”
Section: Parameters and Methodsmentioning
confidence: 99%
“…[13] The intra-band relaxing rate is determined to be 1×10 −13 s. [14] By carefully choosing the specific material parameters, APSYS can be used to explore the internal physical process and in optimizing device performances. [15,16]…”
Section: Parameters and Methodsmentioning
confidence: 99%
“…Nowadays, indium gallium nitride (In x Ga 1−x N) alloys have attracted a lot of attention for optoelectronic applications [1][2][3] due to their tunable energy band gap varying from 0.7 eV to 3.4 eV. [4][5][6][7][8][9] The absorption range covers a major portion of the solar spectrum, making In x Ga 1−x N a promising candidate for multi-junction solar cell systems. In addition, with high radiation resistance, thermal stability and chemical tolerance, InGaN solar cells could operate under extreme environments.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, structural and optical properties of InGaN have aroused great interest because of its widespread applications in light-emitting devices such as light-emitting diodes (LEDs) and laser diodes. [1][2][3][4][5][6] Meanwhile, high emission efficient InGaN is proposed as a potential novel fluorescent material for field emission display (FED), which is possible to work at a low acceleration voltage (42 V) compared with the traditional phosphor. [7] It has also been reported that InGaN material was introduced into a single chip white light emitting diode as an underlying layer (UL) embedded below an active layer of InGaN/GaN multiple quantum wells, and the quality of the white light could be controlled by modulating the relaxation degree of the InGaN UL.…”
Section: Introductionmentioning
confidence: 99%